المعيار المالي في قانون الصفقات العمومية - - عزة لعمارة - نسرين علي شيكوش (جامعة المسيلة, 2022)
يهدف تنظيم الصفقات العمومية إلى إلزام المصالح المتعاقدة في إبرامها لجملة من الإجراءات الشكلية والإجراءات المكيفة والتي تحددها العتبة المالية التي أصبحت في ظل المرسوم 15-247 المتضمن تنظيم الصفقات العمومية وتفويضات المرفق العام . كما أن السعر قد أعطى للصفقة العمومية نظاما قانونيا ميزها عن باقي العقود الإدارية سواء من حيث طريقة الإبرام ، أو من حيث تنفيذها ، حيث أن المشرع ضبط الحلول القانونية في حالة حدوث تغيرات اقتصادية بتطبيقه وسائل تعديل السعر Rusem Organising the public deals aims to oblige contracting favours to make formal and framed procedures that are identified by financial thresholds according the ministerial decree 15-247 which includes: organising public deals and accreditation of public utility. The price gave the public deals a legal system that characterises it from other administrative contracts, whether in making contract or executing it, and also the legislator rectifies the legal solutions in case of the occurrence of economic change by applying the media of rectifying the price.
Keywords: المعيار المالي- قانون الصفقات العمومية